Interactive Effects of Copolymers and Nano-Sized Pigments on Coated Recycled Paperboards in Flexographic Print Applications - Sonmez, Sinan (Asian Journal of Chemistry, 2011)
The object of this study is to show the effects of two different copolymers with coating pigments on flexography. For this purpose, recycled base paperboard was coated with four coating formulations that contain nano-sized clay and ground calcium carbonate using styrene/n-butyl acrylate and acrylic/vinyl acetate copolymers. As a reference, conventional clay and ground calcium carbonate pigments with the same copolymers were also applied. Optical and physical properties of coated recycled paperboards were compared. The coated samples were then printed with a water based flexographic ink using a laboratory K-proofer press. Printability properties were then measured and compared. It was found that the use of styrene/n-butyl acrylate copolymer resulted in an increased print density, print gloss, print chroma and a decreased print mottle. However, the use of acrylic/vinyl acetate copolymer increased the PPS porosity and permeability properties of coated recycled paperboards. As a result, print densities of coated recycled paperboards decreased. In addition, the use of acrylic/vinyl acetate copolymer decreased print chroma and increased print mottle. Although the use of nano-sized clay with styrene/n-butyl acrylate had no significant effect. The use of nano-sized ground calcium carbonate with styrene/ n-butyl acrylate copolymer significantly increased print chroma and decreased print mottle.